2017
DOI: 10.1007/s12039-017-1295-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and photoluminescence properties of tetra(aminophenyl) porphyrin covalently linked to multi-walled carbon nanotubes

Abstract: Synthesis of a new nano hybrid of 5,10,15,20-mesotetra(4-aminophenyl) porphyrin (TAP) functionalized with multi-walled carbon nanotubes (MWCNTs) through an amide linkage is reported for the first time. This MWCNT-TAP hybrid was characterized by Raman, Fourier transform infrared (FT-IR), Transmission electron microscopy (TEM), Thermogravimetric analysis (TGA), absorption and emission spectroscopy. TGA analysis reveals that there is a ∼60% weight loss when heated from 150-750 • C, which is attributed to the amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The G peak position of the treated CNTs‐LDHs (1578 cm −1 ) exhibited a shift to lower frequency (≈3 cm −1 ) compared with untreated CNTs‐LDHs (1581 cm −1 ). In general, hybrid carbon nanomaterials exhibit this type of low‐frequency shift (softening) when functionalized with an electron‐donor molecule . The lower frequency shift observed for the treated CNTs‐LDHs confirmed the charge transfer between the nanocomposite and the CNTs, in which aluminum zinc oxide acts as an electron donor and CNTs act as an electron acceptor.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The G peak position of the treated CNTs‐LDHs (1578 cm −1 ) exhibited a shift to lower frequency (≈3 cm −1 ) compared with untreated CNTs‐LDHs (1581 cm −1 ). In general, hybrid carbon nanomaterials exhibit this type of low‐frequency shift (softening) when functionalized with an electron‐donor molecule . The lower frequency shift observed for the treated CNTs‐LDHs confirmed the charge transfer between the nanocomposite and the CNTs, in which aluminum zinc oxide acts as an electron donor and CNTs act as an electron acceptor.…”
Section: Resultsmentioning
confidence: 73%
“…In general,h ybrid carbon nanomaterials exhibit this type of low-frequencys hift (softening)w hen functionalized with an electron-donor molecule. [35,38] The lower frequencys hift observed fort he treated CNTs-LDHsc onfirmed the charget ransfer between the nanocomposite and the CNTs, in whicha luminum zinc oxide acts as an electron donor and CNTsa ct as an electron acceptor.T his lower-frequency shift and the higher ratio of the Da nd Gb and intensitiesr evealed the functionalization and coatingo fC NTsw ith aluminum zinc oxide nanocomposite and confirmed their vital role in accelerating photocatalytic reactions (discussedb elow). This explana- tion agreesw ith the findings of previousr esearchers, who reported that the Gband shifted to al ower wavenumber and the I D /I G ratio increased when CNTsw ere coupled with metal oxides because of the electron-donor characteristics of metal toward the CNTs.…”
Section: Coating Cntsw Ith Nanocompositementioning
confidence: 77%
See 1 more Smart Citation
“…The peaks at 1634 and 1461 cm −1 in CoTPP-NH 2 are assigned to the vibrations of benzene and pyrrole ring skeletons. 32 Thermogravimetric Analysis (TGA). To know the degree of functionalization of porphyrin on MWCNTs, we performed the thermogravimetric analysis technique in a nitrogen atmosphere (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…26 The strong emission peak for the composite MPT is blue-shifted to 601.0 nm without affecting the weaker one at 653.5 nm upon the excitation at 420 nm, which is due to the alteration of the S 1 electronic energy level of TCPP upon the formation of a multilayer TCPP−Sn complex network in the composite. 27 In addition, the formation of the TCPP−Sn complex network also decreases the electron density at the TCPP, which is more conducive to the occurrence of negative solvatochromism, 28 i.e., a blue shift. In addition, as the mass ratio of the MWCNTs increases from 0.2 to 1.0, the fluorescence intensity of MPT is gradually quenched, which is similar to the UV−vis absorption trend, which is ascribed to the photoinduced electron/energy transfer from the TCPP−Sn complex to MWCNTs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%